Próba identyfikacji wczesnośredniowiecznego warsztatu budowlanego ze Strzelna - Hewner, Katarzyna (Nasza Przeszłość: Studia z dziejów Kościoła i kultury katolickiej w Polsce, 1999)
The identification of the early medieval architecture from Strzelno
Keywords: strzelno

Kamennyi votivnyi relef v Stshelȳno - Putsko, Vasilii (Slavia Antiqua, 1999)
Stone votive relief in Strzelno
Keywords: strzelno

Foundations of monasteries by members of the twelfth-century Polish nobility: a selection of cases - Jamroziak, Emilia (Annual of Medieval Studies at CEU, 1998)
Keywords: strzelno

Katalog prepozytów klasztoru norbertanek w Strzelnie od XII wieku do 1837 r. - Kabaciński, Ryszard; Karczewski, Dariusz (Nasza Przeszłość, 1997)
The Norbertine monastery in Strzelno was founded by Piotr Wszeborowic, the voivode of Kuyavia and the castellan of Kruszwica, in the late 1280s. Organizationally, it was subordinated to the monastery of Saint Vincent in Wrocław. The first mention of provosts appears in sources only in 1220. The provosts came to Strzelno mainly from the monastery in Wrocław, but not all of them came from Silesia. With the election of Gregory of Milejów, the period of provosts coming from Polish monasteries, mainly from the middle class, begins. Only in the 16th century did representatives of the nobility appear. From the 14th to the second half of the 16th century, the office of provost in Strzelno was often a step towards promotion to the position of abbot of the monastery in Wrocław. The vast majority of monasteries of the Polish Premonstratensian Circaria did not keep catalogs of their abbots or provosts, which would constitute a valuable source of information about the internal life and traditions of these monasteries. The exception is the chronicle of the abbots of the monastery of St. Vincent in Wrocław, written down by Prior Mikołaj Liebental by 1504 and continued until 1692. In the Norbertine monastery in Strzelno, as in other houses of this rule, the list of local provosts was compiled only in the first decades of the 18th century. This list was made on a blank page of the monastery copier from around 1573. The list of provosts was compiled on the basis of monastic documents and archival materials, as well as the historical memory of the successors in the position of provost. It is therefore necessary to develop a complete catalog of the superiors of the provostship in Strzelno, which would facilitate knowledge of the history of this monastery and contribute to more detailed research on the clergy, especially the monastic clergy. The chronological framework of this catalog is determined by the first mentions of the superiors of the Norbertine monastery in Strzelno and the year 1837, when the monastery was finally liquidated by the Prussian authorities.
Keywords: strzelno

Średniowieczne naczynia ceramiczne z klasztoru norbertanek w Strzelnie - Sułkowska-Tuszyńska, Krystyna (Wydawnictwo Ar-Gos Mariusz Tuszyński, 1997)
Keywords: strzelno

O fundacji klasztoru norbertanek w Strzelnie - Sikorski, Czesław (Z badań nad dziejami klasztorów w Polsce, 1995)
About foundation of norbertine convent in Strzelno
Keywords: strzelno

Technologia, asortyment i funkcja średniowiecznych naczyń ceramicznych używanych w klasztorze norbertanek w Strzelnie, woj: bydgoskie - Sułkowska-Tuszyńska, Krystyna (Garncarstwo i kaflarstwo na ziemiach polskich od późnego średniowiecza do czasów współczesnych : materiały z konferencji, Rzeszów, 21-23 IX 1993, 1994)
Technologie, Assortiment und Funktion mittelalterlicher Keramikgefässe vom Kloster in Strzelno (Wojewodschaft Bydgoszcz)
Keywords: strzelno

On the technology and assortment of the medieval monastery's pottery, on materials from the 12th to 16th centuries excavated in the premonstratensian nunnery in Strzelno - Sułkowska, Krystyna (Religion and belief : a Conference on Medieval Archaeology in Europe, 21-24th September 1992 at the University of York, 1992)
Keywords: strzelno

Charakterystyka stratyfikacji kulturowej wzgórza klasztornego w Strzelnie (woj: bydgoskie) - Dubikajtis, Jerzy; Sulkowska, Grażyna K.; Dubikajtis, Jolanta (Z badań nad średniowieczną architekturą Kujaw i Wielkopolski wschodniej, 1990)
Description of the culture stratification of the monastery hill in Strzelno (Bydgoszcz voivodship)
Keywords: strzelno